Social Policy and Political Trust: Long-Term Effects of Welfare Generosity in Europe. - Gillissen, Matthijs; Goubin, Silke; Ruelens, Anna (Political Studies, 2026)
While some argue that diminishing welfare policies erode political trust, others contend they do not significantly influence support for political institutions. Despite pressures on social spending, a comprehensive examination of the relationship between welfare policies and political trust is lacking. This research analyzes trends in political trust across Europe using Bayesian dynamic latent variable modeling and investigates the impact of within-country changes and enduring between-country differences in social policies on national-level trust. It focuses on cash benefit transfer policies, particularly those addressing for life-course risks and labor market insurance. Results show that structurally generous social policies correlate with higher political trust, but short-term changes in policy generosity do not. Furthermore, the generosity of specific policies does not exhibit a clear direct relationship with national-level trust. Overall, these findings support the skeptical view that more generous welfare policies do not easily foster increased political trust in the short term.